Fatigue during Chest Compression Using a Neonatal Patient Simulator - Enriquez, Diego; Meritano, Javier; Shah, Birju A.; Song, Clara; Szyld, Edgardo (American Journal of Perinatology, 2018)
Objective The objective of this study was to evaluate chest compression (CC) quality and operator fatigue during CC, with coordinated ventilation, on a neonatal simulator and to explore its association with provider aerobic activity and body mass index.Methods This was a prospective observational experimental study on pediatricians, neonatologists, and neonatal nurses who frequently deliver newborns and who have signed the informed consent. Subjects performed CC coordinated with ventilations at a ratio of 3:1 for 10 minutes on a neonatal mannequin. Proxy of fatigue was defined as four consecutive CC below target.Results Forty subjects participated; 62% were women. Twenty one (52%) evidenced weariness, as they performed. No gender-based differences were found in weariness. No subject abandoned the procedure due to fatigue. Subjects who participated in aerobic exercise had a significantly better performance than those who did not participate. Early fatigue was significantly associated with higher BMI. The reduction in effectiveness occurred at a mean time of 7.7 minutes (range 3.5–9 minutes).Conclusion CC performance quality decreased and fatigue was frequent before 10 minutes had elapsed on a neonatal simulator. Provider fatigue was associated with both lack of aerobic activity and BMI ≥ 25. Our findings support the need for guidelines requiring frequent rotation of CC providers during prolonged neonatal resuscitation.
Keywords: neonatal resuscitation; chest compression; fatigue; newborn